Mathematical analysis of AG-TIO2/blood hybrid nanofluid with inclusion of viscous dissipation over a permeable surface - Rahimah, Jusoh; Muhammad Khairul Anuar, Mohamed; Mohd Hisyam, Ariff (Faculty of Science and Technology, UKM, 2023)
The remarkable efficiency of hybrid nanofluids in heat transfer has made them a prominent research topic. This study investigates the boundary layer flow and heat transfer of AgTiO2/blood hybrid nanofluid while taking viscous dissipation into account. The governing partial differential equations of the hybrid nanofluid are transformed into ordinary differential equations using the requisite similarity transformations. The bvp4c function is then used in Matlab to generate numerical and graphical output. The accurate initial guessing values are then used to calculate the dual solutions. The existence of viscous dissipation considerably reduces the rate of heat transfer in this model. The effects of nanoparticle concentration have also been studied. The thickness of the boundary layer diminishes as the suction parameter rises, whereas different patterns of results are obtained as the concentration of argentum and titania nanoparticles changes.